The impact of parental psychological control on adolescents’ physical activity: the mediating role of self-control and the moderating role of psychological capital - Chao Song; Sha Ge; Weipeng Zhang (Frontiers in Psychology)
ObjectiveInsufficient physical activity poses a significant threat to adolescent health. Parental psychological control, as a typical negative parenting style, exerts profound influences on health-related behaviors among adolescents. This study aims to identify and elucidate the specific mechanisms through which parental psychological control impacts adolescent physical activity. Furthermore, it explores the roles of self-control ability and psychological capital in mediating the relationship between parenting styles and adolescent physical activity. The findings of this research seek to provide guidance for family education practices.MethodsA survey was conducted on 1,010 students from the first year of junior high school to the second year of senior high school to assess parental psychological control, physical activity, self-control, and psychological capital. Data analysis and model validation were performed using SPSS 26 and AMOS 24.ResultsA significant negative correlation was found between parental psychological control and adolescents’ physical activity levels. Self-control was observed to partially mediate this relationship, while psychological capital played a negative moderating role in the adverse impact of parental psychological control on adolescents’ physical activity.ConclusionParental psychological control had a negative impact on the level of physical activity among adolescents. Enhancing adolescents’ self-control and psychological capital could serve as potential strategies to mitigate this negative effect, encouraging adolescents to actively engage in physical activities. This paper provided a new theoretical perspective and practical basis for improving family education methods and promoting positive health-enhancing behaviors among adolescents.